OXYGEN ISOTOPIC COMPOSITIONS OF IVA IRON METEORITES: IMPLICATIONS FOR THE THERMAL EVOLUTION DERIVED FROM IN SITU ULTRAVIOLET LASER MICROPROBE ANALYSES - Wang P.L.; Rumble III D.; McCoy T.J. (My University, 2004)
Oxygen isotopic compositions of silicate inclusions in IVA iron meteorites have been measured with an in situ UV laser microprobe technique. The homogeneity of oxygen isotopic compositions within and among individual mineral grains has also been examined. Oxygen isotope fractionations between coexisting mineral pairs were utilized in oxygen isotope thermometry. Our measured Δ17O values, ranging from 0.97 to 1.25‰, are characteristic of a single reservoir and fully confirm the oxygen isotopic similarity between IVA irons and L/LL chondrites. Steinbach and São João Nepomuceno, containing inclusions of two silicate minerals in mutual contact, exhibit a mass-dependent fractionation of 18O/16O between tridymite and bronzite with apparent oxygen isotopic heterogeneity. The SiO2-bearing member, Gibeon, gives homogeneous oxygen isotopic compositions without detectable fractionation of 18O/16O between tridymite and quartz. Oxygen isotope equilibrium temperatures are estimated for coexisting tridymite and bronzite in the same sample slabs or clusters in Steinbach and São João Nepomuceno. The fractionations of 18O/16O between bronzite and tridymite range from 1.6 to 2.3‰ in different sample slabs or clusters. On the basis of the closure temperature concept, cooling rates are estimated at approximately 20 to 1000°C/Myr between 800 and 1000°C, a range of temperatures not accessible to other cooling rate methods. Using the Fast Grain Boundary diffusion model, we have demonstrated that significant oxygen heterogeneity both in tridymite and bronzite is probably due to isotope exchange during cooling between minerals with various grain sizes and mineral abundances in different regions of the samples. The new estimates of cooling rate by oxygen isotope thermometry refine previous cooling curves of IVA irons and support the breakup-reassembly model for the IVA parent body.